2022
DOI: 10.1371/journal.pmed.1003999
|View full text |Cite
|
Sign up to set email alerts
|

High-dose versus standard-dose vitamin D supplementation in older adults with COVID-19 (COVIT-TRIAL): A multicenter, open-label, randomized controlled superiority trial

Abstract: BackgroundVitamin D supplementation has been proposed as a treatment for Coronavirus Disease 2019 (COVID-19) based on experimental data and data from small and uncontrolled observational studies. The COvid19 and VITamin d TRIAL (COVIT-TRIAL) study was conducted to test whether a single oral high dose of cholecalciferol (vitamin D3) administered within 72 hours after the diagnosis of COVID-19 improves, compared to standard-dose cholecalciferol, the 14-day overall survival among at-risk older adults infected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 33 publications
0
31
1
3
Order By: Relevance
“…In contrast, a pilot trial in Spain, in which 76 hospitalised patients were randomised to control (usual care) or supplementation with 0.532 mg of 25(OH)D (calcifediol) on the day of admission, 7 day 3, and day 7, followed by a weekly dose of 0.266 mg until discharge, observed reduced admission to intensive care in the supplemented group (2% vs 50%; p < 0.001) [91]. An open-label trial 8 in France, in which 254 hospitalised patients aged ≥ 65 years were randomised to a single oral dose of 400,000 IU or 50,000 IU of vitamin D 3 , found reduced deaths at 14 days in the high-dose group (6%) compared with the lower-dose group (11%) (p = 0.049) [92]. In addition to the inconsistency in the findings, and some limitations related to trial design in some studies, all used very large bolus doses (i.e.…”
Section: Vitamin D and Risk And Severity Of Covid-19mentioning
confidence: 99%
“…In contrast, a pilot trial in Spain, in which 76 hospitalised patients were randomised to control (usual care) or supplementation with 0.532 mg of 25(OH)D (calcifediol) on the day of admission, 7 day 3, and day 7, followed by a weekly dose of 0.266 mg until discharge, observed reduced admission to intensive care in the supplemented group (2% vs 50%; p < 0.001) [91]. An open-label trial 8 in France, in which 254 hospitalised patients aged ≥ 65 years were randomised to a single oral dose of 400,000 IU or 50,000 IU of vitamin D 3 , found reduced deaths at 14 days in the high-dose group (6%) compared with the lower-dose group (11%) (p = 0.049) [92]. In addition to the inconsistency in the findings, and some limitations related to trial design in some studies, all used very large bolus doses (i.e.…”
Section: Vitamin D and Risk And Severity Of Covid-19mentioning
confidence: 99%
“…Numerous studies have shown that VitD can reduce the risk of acute viral respiratory tract infections and pneumonia. However, the significance of VitD in the treatment of the acquired infections, such as COVID-19, needs to be further investigated particularly in people with low VitD levels at baseline [ 35 ]. VitD opposes the attachment of the virus to the ACE-2 receptors in the pulmonary epithelium [ 36 ].…”
Section: The Role Of Vitamin D In the Protection And Treatment Of Cor...mentioning
confidence: 99%
“…Since the completion of the aforementioned meta-analysis, a number of interventional studies evaluating the impact of vitamin D supplementation on COVID-19 outcomes have been published. [18][19][20][21][22][23][24] All but two of the studies 23,24 found benefits to vitamin D supplementation in patients hospitalized with COVID-19. Of note, bolus dosing was used in both studies that found no benefit, and in the Mariani et al study, baseline 25(OH)VitD levels >30 ng/mL.…”
Section: Clinical Trial Datamentioning
confidence: 99%